Integrating social media-based community of inquiry with theory of planned behavior to promote equitable educational intentions among pre-service teachers in Gilgit Baltistan, Pakistan - Ullah, Imdad; Asghar, Muhammad Zaheer; Barbera, Elena; Cimen, Meltem (Frontiers in Psychology, 2024)
An equitable education system is essential for enabling all students to develop the knowledge and skills necessary to become productive members of society. Pre-service teachers in education play a vital role in fostering equitable educational practices. This research aims to measure the association of the social media-based community of inquiry with pre-service teachers' intentions towards social justice and educational equity. The study focused on pre-service teachers enrolled in the education departments of universities in Gilgit Baltistan (GB), Pakistan. Census sampling was used to include all students enrolled in teacher education departments across the universities in GB. The research utilized a multi-wave survey design, beginning with a baseline survey to assess pre-service teachers' presence on social media. This information guided the design of a community of inquiry on social media, centered around the theme of social justice and equity in education. After four months, a second survey was conducted to measure the association of the community of inquiry with pre-service teachers' intentions towards social justice and equity. For data analysis, the study employed the partial least squares-consistent structural equation modeling (PLSc-SEM) approach. Moreover, the novelty of the study lies in the integration of the community of inquiry framework with the theory of planned behavior. The research findings revealed a significant and positive association between the social media-based community of inquiry and pre-service teachers' attitudes, subjective norms, and perceived behavioral control regarding their intentions to implement social justice and equity in education. These research insights hold potential for the development of prospective teachers and educational leadership with a strong focus on equity. Future research could explore the development of a community of inquiry for pre-service teachers to enhance their mindset and skills for inclusive education. This endeavor aligns with the broader objective of achieving Sustainable Development Goal 4, fostering a more inclusive and equitable educational environment.